2015
DOI: 10.1016/j.chembiol.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Muscular TrkB by its Small Molecular Agonist 7,8-Dihydroxyflavone Sex-Dependently Regulates Energy Metabolism in Diet-Induced Obese Mice

Abstract: SUMMARY Chronic activation of brain-derived neurotrophic factor (BDNF) receptor TrkB is a potential method to prevent development of obesity, but the short half-life and nonbioavailable nature of BDNF hampers validation of the hypothesis. We report here that activation of muscular TrkB by the BDNF mimetic, 7,8-dihydroxyflavone (7,8-DHF), is sufficient to protect the development of diet-induced obesity in female mice. Using in vitro and in vivo models, we found that 7,8-DHF treatment enhanced the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 52 publications
7
60
0
1
Order By: Relevance
“…Together, with other signaling analysis, the authors proposed that post-HI induced ER expression in female hippocampus couples the c-Src kinase to augment the TrkB phosphorylation, thereby reduces the cellular apoptosis and neuronal injury. In our recent study, we found that 7,8-DHF initiates the AMPK/CREB/uncoupling protein 1 (UCP1) pathway to increase the lipid oxidation and energy expenditure in muscle cells (Chan et al 2015). Concurred with these in vitro findings, administration of 7,8-DHF increased the energy expenditure of mice under high-fat diet (HFD) feeding, thus protecting these animals from gaining excess body weight.…”
Section: Sex-specific Functions Of Bdnfmentioning
confidence: 99%
“…Together, with other signaling analysis, the authors proposed that post-HI induced ER expression in female hippocampus couples the c-Src kinase to augment the TrkB phosphorylation, thereby reduces the cellular apoptosis and neuronal injury. In our recent study, we found that 7,8-DHF initiates the AMPK/CREB/uncoupling protein 1 (UCP1) pathway to increase the lipid oxidation and energy expenditure in muscle cells (Chan et al 2015). Concurred with these in vitro findings, administration of 7,8-DHF increased the energy expenditure of mice under high-fat diet (HFD) feeding, thus protecting these animals from gaining excess body weight.…”
Section: Sex-specific Functions Of Bdnfmentioning
confidence: 99%
“…As a bioavailable chemical, 7,8-DHF can penetrate brain blood barrier upon intraperitoneal or oral administration to provoke TrkB and its downstream signaling, such as phosphoinositide 3-kinase/protein kinase B (Akt; Wu et al, 2014), to exert its central role in pathologic conditions. As a consequence of activating TrkB, 7,8-DHF inhibits obesity in female mice (Chan et al, 2015), reduces spine morphology abnormalities in fragile X syndrome (Tian et al, 2015), enhances axon regeneration and muscle renovation after peripheral nerves injuries (English et al, 2013), improves motor function and prolongs survival in Huntington’s disease (Jiang et al, 2013). Furthermore, it can reverse synapse loss and prevent memory deficits in Alzheimer’s disease (AD; Zhang et al, 2014a; Gao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Conceivably, BDNF action in specific neuronal populations may have different, if not opposing effects on energy metabolism. Supporting this notion, the modulation of the BDNF pathway by TrkB agonists in vivo resulted in reduced, unchanged, or even increased food intake in rodents, depending on the pharmacological agent and the route of its administration . Also, peripheral administration of BDNF in non‐human primates led to a gain in appetite and increased adiposity .…”
Section: Discussionmentioning
confidence: 92%